Recent pattern of drug sensitivity of most commonly isolated uropathogens from Central India - Lawhale, Madhuri Ashok; Naikwade, Rahul (International Journal of Research in Medical Sciences, 2017)
Background: The objective of the study is to assess the latest antibiotic sensitivity pattern of most commonly isolated organisms in urinary tract infection (UTI). Widespread and irrational use of antibiotics has led to development of highly resistant microorganisms. As the antibiotic sensitivity patterns of the microorganisms are frequently changing, this study was performed to assess the recent antibiotic sensitivity pattern in urinary tract infection among the human population. Methods: The study conducted from July 2016 to April 2017, in clinical microbiology laboratory, Sara Diagnostics (fully automated) laboratories, Nagpur, Maharashtra, India. 3000 urine samples were studied. The processing of the samples were done by standard microbiological methods. The antibiotic susceptibility was measured by disk diffusion test. CLSI guidelines were used for the antibiotic susceptibility evaluation. Results: Out of these, 1729 (57.63%) samples were culture positive showing significant bacteriuria. The most common bacteria isolated was E. coli (n=1040, 60.15%), followed by Enterococcus spp. (n=275, 15.90%), Klebsiella pneumoniae (n=210, 12.14%), Staphylococcus aureus (n=105, 6.07%) and Pseudomonas spp. (n=50, 2.89%) in this study. The study showed marked resistance to doxycycline, quinolones, cephalosporins and greater sensitivity to nitrofurantoin and fosfomycin, showing them better treatment options. Conclusions: The study confirmed, E.coli is still the most common bacteria to cause UTI, irrespective of geographical area. Nitrofurantoin, fosfomycin showed very high susceptibility to urinary tract infection pathogens, which include most commonly isolated gram-negative bacteria and gram-positive cocci, which were resistant to other various antibiotic groups. Thus, nitrofurantoin and fosfomycin seemed to be promising drugs.